Smart Apps Creator Media to Increase Self-Awareness Career Advanced Study for Twelve-Grade Students of State High School - Setyaningsih, Endah; Asrowi; Sudiyanto (Universitas Pendidikan Ganesha, 2024)
Self-awareness is considered as the ability to recognize oneself. Lack of self-awareness causes a lack of personal information such as strengths and weaknesses, making it difficult to make career decisions. This research aims to develop ESDILA as a Smart Apps Creator (SAC) media to increase career self-awareness for further studies for class XII students at Karangpandan State High School. This type of research is research and development (R&D), using the 3-phase Alessi and Trollip Instructional System Design model procedure. 202 class XII students taken by random sampling participated in the research. The data in this research are alpha test, beta test, and product effectiveness. The data analysis used during development was Aiken's V coefficient for alpha test analysis, descriptive percentages for beta test analysis, as well as independent t-test, paired t-test, and Cohen's d for product effectiveness analysis. The research results show: 1) Expert evaluation in the alpha test shows that ESDILA is accepted; 2) The usability test in the beta test shows that ESDILA meets the usability criteria in the good category; 3) Compared to conventional counseling, ESDILA has been proven to be effective in increasing career self-awareness for further study for class XII students at Karangpandan State High School. So it is concluded that ESDILA is accepted, meets good usability criteria, and can increase students' career self-awareness so that students are able to recognize themselves and are ready to make career decisions for further study.